Complementarity of PALM and SOFI for super-resolution live-cell imaging of focal adhesions - Deschout, Hendrik; Lukes, Tomas; Sharipov, Azat; Szlag, Daniel; Feletti, Lely; Vandenberg, Wim; Dedecker, Peter; Hofkens, Johan; Leutenegger, Marcel; Lasser, Theo; Radenovic, Aleksandra (Nature communications, 2016)
Live-cell imaging of focal adhesions requires a sufficiently high temporal resolution, which remains a challenge for super-resolution microscopy. Here we address this important issue by combining photoactivated localization microscopy (PALM) with super-resolution optical fluctuation imaging (SOFI). Using simulations and fixed-cell focal adhesion images, we investigate the complementarity between PALM and SOFI in terms of spatial and temporal resolution. This PALM-SOFI framework is used to image focal adhesions in living cells, while obtaining a temporal resolution below 10 s. We visualize the dynamics of focal adhesions, and reveal local mean velocities around 190 nm min-1. The complementarity of PALM and SOFI is assessed in detail with a methodology that integrates a resolution and signal-to-noise metric. This PALM and SOFI concept provides an enlarged quantitative imaging framework, allowing unprecedented functional exploration of focal adhesions through the estimation of molecular parameters such as fluorophore densities and photoactivation or photoswitching kinetics.
Keywords: časové faktory; paxilin; Mice; Rats; fibroblasty; Paxillin; Animals; buněčná adheze; Microscopy; krysa rodu Rattus; Time Factors; Cell Adhesion; zvířata; Staining and Labeling; myši; mikroskopie; Fibroblasts; barvení a značení